Efficacy of color discrimination tests used in dentistry. Issue 6 (30th October 2020) - Simionato, Andressa; Pecho, Oscar E.; Della Bona, Alvaro
Abstract: Objective: To evaluate the efficacy of visual discrimination tests used for color research in dentistry. Materials and methods: Volunteers (N = 120) were divided in three groups of observers (n = 40; gender‐balanced): S‐dental students; D‐dentists; and L‐laypersons. Two general color discrimination tests (I‐Ishihara and FM‐Farnsworth‐Munsell 100 Hue) and the test of color discrimination competency in dentistry using the VITA Classical shade guide (VC) were performed and data were recorded according to manufacturers' or literature recommendations. Data were statistically analyzed using Mann–Whitney U test for the gender influence and Kruskal‐Wallis test for the observer influence, and Bonferroni as post‐hoc test (α = 0.05). Pearson (α = 0.05) was used to examine the correlation among visual tests (I, FM, and VC). Results: Observers and visual tests were not influenced by gender ( P  > .05). Different observer groups had no influence on I test ( P  > .05). S and D showed similar level of color perception using FM and VC ( P  > .05), but these observers showed greater color perception than L ( P  ≤ .05). FM and VC also showed significant correlation ( P  ≤ .05) for the overall D observers (r = −0.362), male D (r = −0.594) and female S (r = −0.457). Conclusion: Observer experience significantly influenced on color perception, irrespective of gender. FM test showed greater correlation to color correspondence in dentistry (VC) than I test. Clinical significance: Observer experience is more relevant than gender for the color selection process in dentistry. Considering the visual discrimination tests for color research in dentistry, the Farnsworth‐Munsell 100 Hue test seems to be more efficacious than the Ishihara test.